2003
DOI: 10.1055/s-2003-36799
|View full text |Cite
|
Sign up to set email alerts
|

A First Asymmetric Diamination of Olefins

Abstract: An asymmetric diamination of olefins employing stable imidoosmium(VIII) complexes is described for the first time. The reaction is based on the use of chiral acrylic esters and related substrates with enantiopure menthol and 8-phenyl menthol as chiral auxiliaries and gives rise to osmaimidazolidines with good to excellent diastereomeric ratios (up to 95:5). Removal of the osmium centre and the chiral auxiliary leads to novel enantiopure 1,2,3-trisubstituted compounds.Metal-mediated diamination of unfunctionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…219,220 In common with Sharpless, Muñiz has found that electron-deficient alkenes are the most favored substrates for diamination, but has also demonstrated that in addition to acrylate and cinnamate esters 315 , α,β-unsaturated ketones, aldehydes, amides 318 , nitriles and even 3-pyridyl acrylates are suitable substrates (Scheme 81). 221 Liberation of the 1,2-diamines from their corresponding metallaimidazolidines can be accomplished through reduction with LiAlH 4 or NaBH 4 . 219 …”
Section: Transition Metal-catalyzed Diaminationmentioning
confidence: 99%
“…219,220 In common with Sharpless, Muñiz has found that electron-deficient alkenes are the most favored substrates for diamination, but has also demonstrated that in addition to acrylate and cinnamate esters 315 , α,β-unsaturated ketones, aldehydes, amides 318 , nitriles and even 3-pyridyl acrylates are suitable substrates (Scheme 81). 221 Liberation of the 1,2-diamines from their corresponding metallaimidazolidines can be accomplished through reduction with LiAlH 4 or NaBH 4 . 219 …”
Section: Transition Metal-catalyzed Diaminationmentioning
confidence: 99%
“…Both osmium-and selenium-based reagents have been demonstrated to promote this transformation, but application in synthesis is limited by the stoichiometric nature of these processes and by an abridged substrate scope [106][107][108]. Li has described a rhodium-catalyzed diamination reaction of alkenes using TsNCl 2 as the terminal oxidant (Scheme 17.36) [109].…”
Section: Rhodium(ii)-catalyzed Olefin Diaminationmentioning
confidence: 99%
“…We have previously employed (À)-8-phenylmenthol as auxiliary in asymmetric diaminations with the related bisimido complex. [10,11] In the present case, diamination of (À)-8-phenylmenthyl cinnamate and crotonate yielded four stereoisomers in different ratios of about 7:3:1:1 and 6:3:1:1, respectively. In contrast, (À)-8-phenylmenthyl acrylate 5 a and the corresponding 8-phenylmenthyl methacrylate reacted faster and produced an almost equal mixture of only two diastereomers (ratio = 1:1:0:0) that could be separated by semipreparative HPLC (Scheme 2).…”
mentioning
confidence: 69%
“…Among these reactions, Sharpless dihydroxylation and aminohydroxylation have been highly acclaimed, [8] whereas related diamination reactions have received only scant attention. [9][10][11] We have recently reported on the stereoselective diamination of olefins by reaction of bis(N-tert-butylimido)dioxoosmium(viii) with fumaric and acrylic ester derivatives [10] to give stable monomeric osmaimidazolidines.[11] When the corresponding trisimidoosmium complex 1 is allowed to react with unsymmetrical esters such as methyl cinnamate 2 a, clean formation of two new compounds is observed (Scheme 1). These were identified as a pair of diastereomeric chiral-at-metal osmaimidazolidines.…”
mentioning
confidence: 99%
See 1 more Smart Citation